Two new species and four new records of the Sarsia tubulosa group of Sarsia (Cnidaria, Corynidae) from the Bohai Sea of China - Wang, Xiao; Chen, Xiao-Yin; Xu, Zhen-Zu (Zootaxa, 2022)
Seven species of the Sarsia tubulosa group in the Sarsia genus from the Bohai Sea of China are described in the present paper. These include two new species, namely Sarsia bohaiensis Xu, Wang, & Chen sp. nov. and Sarsia macrogastera Xu, Chen, & Wang sp. nov., and four new records to China, namely Sarsia apicula (Murbach & Shearer, 1902), Sarsia piriforma Edwards, 1983, Sarsia striata Edwards, 1983 and Sarsia viridis Brinckmann-Voss, 1980. In addition, Sarsia tubulosa (M. sars, 1835) is a new record to the Bohai Sea of China. A key to all known species of the Sarsia tubulosa group is provided. The specimens examined in the study have been deposited at the First Institute of Oceanography, Ministry of Nature Resources.